The Inflection of Latin Proper Names in the Old English Translation of Bede’s Historia Ecclesiastica - Esaúl Ruiz Narbona (Languages, 2024)
This paper discusses the inflections of Latin proper names in the Old English translation of Bede’s Historia Ecclesiastica. Whereas most common Latin loans are integrated into the Old English system as far as inflections are concerned, proper names, like scientific loans, can retain Latin inflections in some contexts. The analysis of the more than 700 tokens in this text reveals that the prototypical paradigm of Latin proper names results from a mixture of Latin and Old English patterns. The choice of inflections seems to be chiefly conditioned by grammatical case. While the nominative and accusative are modeled after Latin with very few exceptions, the dative and genitive are influenced by Old English paradigms as well. Both Latin and Old English inflections are evenly distributed in the dative. However, marking on names seems to be secondary and determined primarily by additional morphosyntactic means such as determiners or prepositions. As for the genitive, the predominant inflection, thematic vowel plus -s, results from the fusion of the inflections in both languages grounded in phonetic or spelling similarities.